Structural-functional model of medical students’ professional-applied physical training - A.V. Petryshyn (Physical Education of Students)
Purpose: to work out and experimentally prove model of professional-applied physical training of medical higher educational establishments’ students. Material: in the research 80 students participated. In questioning physical education instructors of medical higher education establishments (n=20) participated. Results: influence of students’ professionally important characteristics on general physical fitness indicators and functional state has been shown. Directions of students’ physical fitness parameters’ individual diagnostic and control over physical education effectiveness have been offered. Volumes of physical exercises in the structure of training have been found: special training (15-20%) and competition exercises (20-30%). Conclusions: the need in raising the level of professionally important for students’ abilities has been noted: speed power, static power endurance, power endurance, coordination of arms’ movements, static balance.